Separation with Estimation of High Molecular Weight Isoenzyme in Breast Cancer Patients (Journal of the College of Basic Education, 2022)
Total alkaline phosphatase (ALP) was measured in two groups of breast cancer patients, group 1 consisted of 27 patients with axillary metastases, group 2 consists of 4 patients with liver metastases .In addition , a group of control subjects was included . The results showed that total serum ALP was especially increased in group 2. ALP was purified from sera of patients with breast cancer by gel filtration on a sepharose CL-6B(106+30)cm and high molecular weight alkaline phosphatase isoenzyme (HALP) was isolated at pH 7.4.